Real-time finger motion recognition using skin-conformable electronics - Cho, Haein; Lee, Inho; Jang, Jingon; Kim, Jae Hyun; Lee, Hanbee; Park, Sungjun; Wang, Gunuk (Nature Electronics, 2023)
Interpreting and tracking finger motion in free space is of use in the development of control interfaces for augmented and virtual reality systems. One approach to create human–machine interfaces capable of accurate finger motion recognition is to use wearable sensors with integrated neuromorphic computing. Here we show that an integrated titanium-oxide-based artificial synapse array and organic motion sensor can be conformably attached to a finger and provide real-time motion recognition. The synaptic device and sensor exhibit well-defined synaptic and light-responsive electrical properties, respectively, as well as flexibility and mechanical robustness. The integrated synapses–sensor enables optical–electrical signal conversion and summation of post-synaptic current. Finger motions for time-resolved digit patterns (0–9) can be learned and recognized with an accuracy of up to 95% at varying strains and up to 100 strain cycles.
Keywords: Augmented and virtual realities; Augmented reality systems; Control interfaces; Finger motion; Finger motion recognition; Free spaces; Human Machine Interface; Neuromorphic computing; Real- time; Virtual reality system